Mindful parenting sebagai pendekatan untuk mengatasi work-family conflict pada ibu bekerja - Dewi, Rini Liana; Riady, Muhammad Antos; Sari, Putri Puspita; Hanifah, Rulia (JOURNAL OF Mental Health Concerns, 2025)
Background: Working mothers face challenges in juggling their dual roles as employees and primary caregivers at home, which often leads to work-family conflict. This conflict is exacerbated by feelings of guilt for not being able to fully accompany their children, as well as concerns about the quality of substitute care. Purpose: To examine the relationship between mindful parenting and work-family conflict among working mothers who leave their children in childcare, in order to determine the extent to which mindful parenting can contribute to reducing conflict between work and family demands. Method: The approach used in this study was quantitative with a correlational design involving working mothers who left their children in Aceh. The instruments used were the Mindful Parenting Questionnaire and the Work-Family Conflict Scale.Results: Pearson's correlation test showed no significant relationship between mindful parenting and work-family conflict, indicating that mindful parenting is not the only factor that influences the role conflict of working mothers.Conclusion: These findings open up opportunities to explore other factors that contribute to work-family conflict. Keyword: Mindful Parenting; Working Mother; Work-Family Conflict. Pendahuluan: Ibu bekerja menghadapi tantangan dalam menjalani peran ganda sebagai pekerja dan pengasuh utama anak di rumah yang kerap menimbulkan work-family conflict. Konflik ini diperburuk oleh perasaan bersalah karena tidak dapat mendampingi anak secara penuh, serta kekhawatiran terhadap kualitas pengasuhan pengganti. Tujuan: Untuk mengkaji hubungan antara mindful parenting dan work-family conflict pada ibu bekerja yang menitipkan anak, guna mengetahui sejauh mana kesadaran penuh dalam pengasuhan dapat berkontribusi dalam menurunkan konflik antara tuntutan pekerjaan dan keluarga. Metode: Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif dengan rancangan korelasional dengan partisipan ibu bekerja yang menitipkan anak di Aceh. Instrumen yang digunakan adalah Mindful Parenting Questionnaire dan Work-Family Conflict Scale. Hasil: Uji korelasi Pearson menunjukkan tidak terdapat hubungan signifikan antara mindful parenting dan work-family conflict yang mengindikasikan bahwa mindful parenting bukan satu-satunya factor yang memengaruhi konflik peran ibu bekerja.Simpulan: Temuan ini membuka peluang untuk menelusuri factor-faktor lain yang berkontribusi terhadap work-family conflict. Kata Kunci: Ibu Bekerja; Mindful Parenting; Work-Family Conflict.